2012
DOI: 10.1364/josab.29.000274
|View full text |Cite
|
Sign up to set email alerts
|

Room-temperature strong terahertz photon mixing in graphene

Abstract: We demonstrate that single layer graphene exhibits a strong nonlinear photon-mixing effect in the terahertz frequency regime. Up to room temperature, the third-order nonlinear current in graphene grows rapidly with increasing temperature. The third-order nonlinear current can be as strong as the linear current under a moderate electric field strength of 10 4 V∕cm. Because of the unique Dirac behavior of the graphene quasi-particles, low Fermi level and electron fillings optimizes the optical nonlinearity. Unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
31
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 32 publications
3
31
0
Order By: Relevance
“…This peculiar quasiparticle nature has resulted in many interesting optical properties in graphene [3][4][5][6][7][8][9][10][11]. Graphene absorbs only 2.3% of the incident light in its pristine form [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This peculiar quasiparticle nature has resulted in many interesting optical properties in graphene [3][4][5][6][7][8][9][10][11]. Graphene absorbs only 2.3% of the incident light in its pristine form [4].…”
Section: Introductionmentioning
confidence: 99%
“…The optical conductance can, however, be significantly enhanced by cutting graphene into nano-scale ribbon [5,6]. The exceptionally strong nonlinear multiple-photon coupling of graphene in the terahertz (THz) frequency regime is another manifestation of the linear energy spectrum [7][8][9]. Surprisingly, the strong THz optical nonlinearity is wellpreserved even in its bi-layered form [10] and in the case of a finite bandgap opening [11].…”
Section: Introductionmentioning
confidence: 99%
“…However, we note that most of the present theoretical and experimental works paid more attention to the real part of the nonlinear refractive index. [24][25][26][27][28][29][30][31][32] Some of us have recently conducted an in-depth study of the nonlinearity of graphene by taking into account the effects of finite temperature and phenomenological relaxation. 33 We found that the consideration of the imaginary part of the nonlinear index, i.e., the nonlinear absorption, would significantly change the evaluation of the nonlinear performance, which will be shown in detail in our analysis below.…”
mentioning
confidence: 99%
“…The simplest model to describe the nonlinear optical response of graphene is through the Boltzmann transport equation [58][59][60]68], generally written as follows: where v g is the group velocity derived from the semi-classical dispersion relation…”
Section: Nonlinear Optical Properties Of Graphene (A) Theoretical Stumentioning
confidence: 99%